2014
DOI: 10.1155/2014/623742
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependent Optical Nonlinearity and Optical Limiting Properties of Water Soluble CdSe Quantum Dots

Abstract: We present third-order optical nonlinear absorption in CdSe quantum dots (QDs) with particle sizes in the range of 4.16-5.25 nm which has been evaluated by the -scan technique. At an excitation irradiance of 0.54 GW/cm 2 the CdSe QDs exhibit reverse saturation indicating a clear nonlinear behavior. Nonlinearity increases with particle size in CdSe QDs within the range of our investigations which in turn depends on the optical band gap. The optical limiting threshold of the QDs varies from 0.35 GW/cm 2 to 0.57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…For calculating the 1s-1s electronic transition in spherically layered semiconductor quantum dots extended theoretical approach was introduced by A. Eychmüller et al [167]. Venkatram et al reported that CdSe nanoparticles of different sizes show multiphoton absorption under 800 nm excitation [168]. The particle size ranging from 4.16 to 5.25 nm of CdSe QDs exhibits reverse saturable absorption under 532 nm laser excitation and the two-photon absorption (TPA) coefficient values enhance when decreasing the bandgap [137].…”
Section: Uses Of Core-shell Quanutm Dots As Optical Gain and Lasing Applicationsmentioning
confidence: 99%
“…For calculating the 1s-1s electronic transition in spherically layered semiconductor quantum dots extended theoretical approach was introduced by A. Eychmüller et al [167]. Venkatram et al reported that CdSe nanoparticles of different sizes show multiphoton absorption under 800 nm excitation [168]. The particle size ranging from 4.16 to 5.25 nm of CdSe QDs exhibits reverse saturable absorption under 532 nm laser excitation and the two-photon absorption (TPA) coefficient values enhance when decreasing the bandgap [137].…”
Section: Uses Of Core-shell Quanutm Dots As Optical Gain and Lasing Applicationsmentioning
confidence: 99%
“…Результаты экспериментов по оптическому ограничению для системы ЖК-WS 2 наночастицы приведены на рис. 1, а также в сравнительной таблице [10,[16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: результаты и обсуждениеunclassified
“…It is well-known that the transitions between different electronic states in QD nanostructures can be optically excited by laser fields. In this context, studying nonlinear optical process, including RSA and saturable absorption (SA) have been pursued by several researchers [29][30][31][32] ; for example, the intensity-dependent nonlinear absorption and nonlinear refraction of QDs were experimentally investigated in Ref. 29 .…”
mentioning
confidence: 99%